As águas subterrâneas de Belém e adjacências: influência da Formação Pirabas e parâmetros físico-químicos para medidas de qualidade - SAUMA FILHO, Michel (Universidade Federal do Pará, 2022)
In the Metropolitan Region of Belém (PA) the water supply to the population comes from springs (physiographic area of ​​Utinga) and from a network of positional tube wells, in general, in more remote urban areas or where pumping is precarious. This work evaluates the groundwater used in the Metropolitan Region of Belém, correlating data of physical, physical-chemical and chemical parameters, in an attempt to compose an understandable picture about the quality of these waters, and to verify the influence that they suffer from the geological units in which they are located. the aquifers that preserve them are located. To carry out the work, water samples were collected in two different seasonal periods: dry and rainy. After exhaustive consultation of the files of companies, institutions and researchers, 17 tubular wells were selected, 9 in Belém, 5 in Icoaraci, 2 in Mosqueiro and 1 in Ananindeua (Annex A). The most frequent turbidity indices were between 9 and 14 units (ppm of SiO2), but some wells showed higher values ​​(33, 41 and 71 ppm of SiO2. Only in some cases, this turbidity can be immediately correlated with the silica content obtained by chemical analysis. The most frequent color measurements are in the range from zero to 7.5 U.C., with the zero index predominating. However, some wells showed a value above 100 U.C. and others, less frequent, with indices varying between 20 and 60 U.C. The pH and electrical conductivity were quite different parameters. Thus, the highest pH and electrical conductivity indices were verified in the aquifers of the Pirabas Formation. In these cases, the pH was around 6 .4 to 7.6 and conductivity between 231 and 362 µS/cm, with a discontinuity at 87.5 µS/cm, also attributed to a well associated with the aforementioned Formation. More acidic waters (pH below 6.38 and above of 4.01) are certainly attributed to the aquifers of the Barreiras and Post-Barreiras Group. The chemical constituents, notably the contents of Ca2+, Mg2+, Na+ and K+, are consistent with the interpretation of the numerical values ​​of pH and electrical conductivity. Without exception, the concentrations of Ca2+ are higher than those of the other cations, establishing a decreasing order according to Ca2+> Mg2+> Na+>K+, with some inversion between Na+ and Mg2+. The highest concentrations of Ca2+ (soon followed by Mg2+) result from the dissolution of carbonates present in the Pirabas limestone. In fact, confirming this assertion, the concentrations of HCO-3 are also much higher than the concentrations of Cl- and SO2-4. It is to be expected, therefore, that the dissolution of Pirabas sediments produces higher concentrations of Ca2+ and HCO-3. The silica and iron contents also discriminate such waters. In general, higher silica contents correspond to greater depths, as would be expected, taking into account the action of chemical weathering on silicate minerals. As for iron, this constitutes a differentiating parameter of the waters of the Pirabas Formation, almost always at much lower levels than the corresponding values ​​associated with the Barreiras and Post-Barreiras aquifers, with, however, exceptions, in which appreciable indices of iron related to Pirabas sediments. It should be noted that the Pirabas Formation appears in the Metropolitan Region of Belém almost always at depths greater than 100 m, although there are records of smaller depths, but these are apparently rarer situations, as is the case with well number 3. , on the University Campus, near the Guamá River, with a depth of 76 m, and the 94 m well of the Museu Paraense Emílio Goeldi, in the central area of ​​the city (Annex A). The exhaustive consultation of the aforementioned archives of institutions, companies and researchers led to the realization that many tubular wells installed in the urban area use water associated with the Barreiras and Post-Barreiras aquifers, where the pH values ​​are almost always, below 6 units, and electrical conductivity measurements rarely reach 100 µS/cm. Finally, it appears that there is a need for greater investments in order to increase the prospection and use of groundwater in the region, as these, in addition to dispensing with treatment prior to distribution, are still a source of resources, not dimensioned, but of great potential.